2007
DOI: 10.1016/j.jplph.2006.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase activity decrease during acclimation to hyposaline conditions in marine seaweed Grateloupia doryphora (Rhodophyta, Halymeniaceae)

Abstract: SummaryPolyamines (PAs), such as diamine putrescine (PUT), triamine spermidine (SPD) and tetraamine spermine (SPM) have been related to environmental stress, including salt stress. A marine red macrophyte alga Grateloupia doryphora (Montagne) Howe was used to investigate the role of PAs during acclimation to moderate hyposaline conditions (incubation 24 h in 18 psu seawater as compared to 36 psu of natural seawater). The results obtained showed that a moderate hyposaline shock caused an increase in the free fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…They suggested that free-Spd, free-Spm and PIS-bound Put facilitated the osmotic stress tolerance of wheat seedlings. Garcıa-Jimenez et al 38 reported that a moderate hyposaline shock caused an increase in the free fraction of Put, Spd and Spm, mainly due to a decrease in TGase activity, together with an apparent increase in the L-arginine dependent PAs synthesis (ODC and arginase decreased, and ADC slightly increased).…”
Section: Polyamines and Abiotic Stress Tolerance In Plantsmentioning
confidence: 99%
“…They suggested that free-Spd, free-Spm and PIS-bound Put facilitated the osmotic stress tolerance of wheat seedlings. Garcıa-Jimenez et al 38 reported that a moderate hyposaline shock caused an increase in the free fraction of Put, Spd and Spm, mainly due to a decrease in TGase activity, together with an apparent increase in the L-arginine dependent PAs synthesis (ODC and arginase decreased, and ADC slightly increased).…”
Section: Polyamines and Abiotic Stress Tolerance In Plantsmentioning
confidence: 99%
“…In algae, there are data on the endogenous levels of polyamines in several green, red and brown algae (Badini et al 1994;Marián et al 2000a). These polyamines are involved in cell division (Cohen et al 1984;García-Jiménez et al 1998;Marián et al 2000b;Voigt et al 2000;Theiss et al 2002), and in response to hyposaline stress (Lee 1998;García-Jiménez et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies involving red seaweeds have demonstrated the metabolism of polyamines mediated by activities of ornithine decarboxylase, diamine oxidase, and polyamine oxidase (Garcia‐ Jimenez et al. , Sacramento et al. , Sacramento et al.…”
Section: Resultsmentioning
confidence: 99%